THE EFFECT OF TOMATO EXTRACT (Lycopersicon esculentum) ON THE FORMATION OF ATHEROSCLEROSIS IN WHITE RATS (Rattus norvegicus) MALE - R. N. Selamet; Sugito Sugito; Dasrul Dasrul (Jurnal Natural, 2013)
The aim of this research was to find out anti-cholesterol activity intomato extract (Lycopersicon esculentum) on blood lipid profile and its potential application in the prevention of atherosclerosis in rats fed with high cholesterol diet. This research employed a complete randomized design with unidirectional pattern by using white rats (Rattus norvegicus) divided into five groups. Negative control group was fed with standard diet, while positive control groups were fed with high cholesterol (hypercholesterolemia) diet, group K were fedwith tomato extract at a dose of 10, 20, and 40 mg/kg together with high cholesterol diet. The result of this researchshowed that high cholesterol diet fed decreased simultaneously with tomato extract at a dose of 10, 20, and 40 mg /kg of rats after 60 days of treatment. Tomato extract was able prevent the formation of plaque in the coronary arteries of rats fed with hypercholesterolemia diet. Effective dose oftomatoextractused in this study was 20-40mg/kg.